Teacher learning in Malaysia: Problems and possibilities of reform, - Raman, Santhiram (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Teacher learning and continuous teacher professional development have become important topics in educational research in view of the ongoing pressure for change in education. It is all the more important because educational reforms require both changes in teachers’ ways of thinking about student learning and changes in their teaching practices. (Meirink, J.A., Imants, J., Meijer P.C. & Verloop, N., 2010). The effective schools research has also cited strong leadership focusing on instruction as a contributing towards good schools, thus underscoring the need for heads exhibiting purposeful leadership focusing on instruction (Fullen, 1991)